The SERENADE project – A step forward in the Safe by Design process of nanomaterials: Moving towards a product-oriented approach. (August 2021) - Rose, Jerome; Auffan, Melanie; De Garidel-Thoron, Camille; Artous, Sebastien; Brochard, Gregory; Clavaguera, Simon; Truffier-Boutry, Delphine; Wortham, Henri; Masion, Armand
Highlights: Current Safe by Design implementation strategies lack flexibility. Product oriented Safe by Design appears as efficient solution. Sequential Safe by Design strategies focusing on the nanomaterial may prove inadequate. Graphical Abstract: ga1 Abstract: Recent research efforts have gone into formalizing and standardizing the Safe by Design process of nanomaterials. This usually results in a structured and (most often) sequential approach deliberately putting the focus on hazard and exposure issues regarding the nanomaterial itself in a bottom-up progression of material development. However, this general strategy lacks flexibility. Within the project SERENADE, a case study examining photocatalytic paint failed to validate the generally accepted Safe by Design scheme. This example examined the product (paint in this case) rather than the nanomaterials it contains. It was found that the essential parameters, namely product specification and functionality, failed to fit into a rigid bottom-up approach and indicated the need for alternative Safe by Design strategies.